Universiti Teknologi PETRONAS Energy Retrofitting: Turning Challenges into Opportunities - Khamidi, M. Faris (2010)
High Building Energy Index (BEI) reported for Universiti Tecknologi PETRONAS (UTP) shows that there are issues pertaining to the electricity consumption of the buildings in the campus. Thus this study investigates the root cause of the inefficient electricity consumption of UTP buildings. Initially, survey methods that include walk-through of the buildings are used to gather relevant information pertaining to energy apportioning. Due to the restricted availability of the data, three buildings, namely Building 13, 14 and Pocket C were chosen from the new academic complex to represent the whole UTP. In addition, structured questionnaires were distributed among the end-users of the three buildings to determine information regarding energy consumption from their perspective. The results established that building survey, energy apportions and performance monitoring approach is a suitable method to investigate the root cause and potential solution to retrofit the UTP buildings. Finally, by identifying all the possible challenges, opportunities on energy saving is identified for retrofitting to significantly reduce the overall BEI of UTP buildings.